ORIENTASI TEKNOLOGI MELALUI PEMAHAMAN DIGITAL MARKETING TERHADAP PENINGKATAN PENDAPATAN PETANI MILENIAL DI KECAMATAN SEBATIK KABUPATEN NUNUKAN PROVINSI KALIMANTAN UTARA - Rusdy Setiawan; Etty Wahyuni; Irawati HM; Yusrie Yusrie (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2026)
Agriculture in Indonesia in 2020-2024 is focused on realizing advanced, independent, and modern agriculture, with one of the main targets being the growth of 2.5 million millennial entrepreneurs by 2024. In North Kalimantan, millennial farmers have a strategic role in achieving food sovereignty, but many of them have not utilized digital technology for marketing. Digital marketing is very important because it can significantly increase farmers' income by expanding market reach, increasing product visibility, and facilitating consumer access to agricultural products. This study aims to analyze the effect of technology orientation through digital marketing on increasing the income of millennial farmers in Sebatik District, Nunukan Regency. Based on the Technology Acceptance Model (TAM) theory, this study examines the relationship between technology orientation, perceived ease of use, perceived usefulness, behavioral intention to use, actual system use, and farmers' income. A quantitative approach with a survei method was used to collect data which was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS application. The results showed that technology orientation has a positive effect on the use of digital marketing (actual system use), which further increases farmers' income. The use of digital marketing can expand the market and increase the visibility of farmers' products, thereby driving an increase in their income. This study also found that technology orientation has a positive effect on farmers' income through digital marketing as a mediating variabel. These findings suggest that the adoption of digital technology plays a key role in improving the welfare of millennial farmers. As a recommendation, the researcher suggests that the government and relevant stakeholders provide ongoing training and technical support to millennial farmers in adopting digital marketing, as well as develop adequate digital infrastructure to support online marketing of agricultural products.